The SWC4 subunit of the SWR1 chromatin remodeling complex is involved in varying virulence of Metarhizium brunneum isolates offering role of epigenetic regulation of pathogenicity. Issue 1 (31st December 2022) - Reingold, Victoria; Staropoli, Alessia; Faigenboim, Adi; Maymone, Marcel; Matveev, Sabina; Keppanan, Ravindran; Ghanim, Murad; Vinale, Francesco; Ment, Dana
ABSTRACT: The host – pathogen interaction is a multifactorial process subject to a co-evolutionary arms race consisting of rapid changes in both host and pathogen, controlled at the genetic and epigenetic levels. Previously, we showed intra-species variation in disease progression and pathogenicity in aphids for Metarhizium brunneum isolates MbK and Mb7. Herein, we compared genomic, epigenetic, and metabolomic variations between these isolates and their effects on pathogenicity. Genomic variation could not completely explain the observed differences between the isolates. However, differential N6-adenine methylation (6 mA) and its correlation to reduced expression of the essential SWC4 subunit of SWR1 chromatin-remodelling complex (SWR1-C) led us to hypothesize a role for swc4 in the varying pathogenicity. Mutagenesis of the essential swc4 gene in MbKisolate resulted in reduction of secondary-metabolite (SM) secretion and impaired virulence in Galleria mellonella . Our results suggest the role of SWC4 in the regulation of SMs and the role of both SWC4 and SWR1-C in virulence of M. brunneum isolates. A better understanding of epigenetic regulation of SM production and secretion in entomopathogenic fungi may enable theirmanipulation for better biocontrol performance, and expand possibilities for environmentally friendly pest control.